Awareness Regarding Stroke among Adults in a Rural Community of Western Nepal - Pandeya, Bishnu; Mukhia, Suzanna; Koirala, Manisa (Journal of Nursing Education of Nepal, 2023)
Introduction: Stroke is the second most common major cause of disability and death worldwide. Identification of risk factors and symptoms is a major focus, directed toward seeking early management. This study was intended to assess the awareness regarding stroke among adults residing in a community in western Nepal. Methods: A descriptive cross-sectional study was conducted among 251 adults residing in Kaligandaki Rural Municipality, Syangja, Nepal. Data were collected using probability, systematic random sampling techniques through a semi-structured interview schedule and analyzed in SPSS version 16 by using descriptive and inferential statistics. Results: The study showed that the correct meaning of stroke was stated by 78.9% of respondents; 88.8% said the brain was the main organ affected. Likewise, 89.2% of respondents mentioned high stress, 84% high blood pressure, and 82% advanced age as the main risk factors for stroke. The majority (82.5%) of the respondents said severe headaches, sudden facial drops, arm or leg weakness (80.5%), and dizziness (85.7%) were the warning signs of stroke. Very few (9.6%) of the respondents had good awareness; 75.3% had an average level of awareness regarding stroke. A statistically significant association was found between level of awareness with ethnicity (p< 0.001) and educational level (p<0.001) of respondents on stroke. Conclusion: Very few adults in a community have a good level of awareness, so a community-level awareness program is recommended to raise awareness regarding stroke. DOI: https://doi.org/10.62143/3vx7nn20